Capacity Building UMKM Pendukung Area Wisata Museum Kereta Api Ambarawa - Lasti Satiani; Dian Novita Kristiyani (Universitas Kristen Satya Wacana Salatiga, 2025)
Capacity building of MSME partners in tourist areas is one of the essential things in improving services in tourist areas. The Ambarawa Railway Museum must pay attention to the governance of MSME partners in the museum area. The management of the Ambarawa Railway Museum is trying to organize MSMEs to provide good service to tourists. MSME partners still face many obstacles in running their businesses, such as limitations in marketing, service, product innovation, communication skills, product selection, and marketing strategies. The purpose of this community service is to provide increased capacity for MSME partners related to entrepreneurship and excellent service. This activity was carried out on December 11-12, 2024. This capacity increase can improve the understanding and capacity of MSME partners at the Ambarawa Railway Museum and answer the challenges of partners. With this activity, the recommendation given for the next activity is assistance from the capacity-building activities that have been carried out so that MSME partners in the tourist area can support the running of tourism activities at the Ambarawa Railway Museum.